2019
DOI: 10.1371/journal.pbio.3000140
|View full text |Cite
|
Sign up to set email alerts
|

A novel nonosteocytic regulatory mechanism of bone modeling

Abstract: Osteocytes, cells forming an elaborate network within the bones of most vertebrate taxa, are thought to be the master regulators of bone modeling, a process of coordinated, local bone-tissue deposition and removal that keeps bone strains at safe levels throughout life. Neoteleost fish, however, lack osteocytes and yet are known to be capable of bone modeling, although no osteocyte-independent modeling regulatory mechanism has so far been described. Here, we characterize a novel, to our knowledge, bone-modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 57 publications
0
39
0
Order By: Relevance
“…Of the two preinjury subgroups, M-2 represented the mature bone lineage, which was enriched for expressions of bglap, mgp, and sost ( fig. S6E) (36,37). Comparing to M-2, cluster M-1 presented low expression levels of bglap, mgp, and sost and high expression levels of a group of other genes, including fhl1a, fhl2a, and tagln ( fig.…”
Section: Mesenchymal Regenerations-building and Supporting The Bonementioning
confidence: 95%
“…Of the two preinjury subgroups, M-2 represented the mature bone lineage, which was enriched for expressions of bglap, mgp, and sost ( fig. S6E) (36,37). Comparing to M-2, cluster M-1 presented low expression levels of bglap, mgp, and sost and high expression levels of a group of other genes, including fhl1a, fhl2a, and tagln ( fig.…”
Section: Mesenchymal Regenerations-building and Supporting The Bonementioning
confidence: 95%
“…The presence of lower jaw cartilages in which loading can be manipulated allows miRs which are responsive to mechanical load to be isolated (Chen et al 2005 ) and identified so that specific pathways can be dysregulated through CRISPR/cas9-induced mutation of miR signalling pathway components or through immersion in miR agonists/antagonists and the effect on chondrocytes studied. Other skeletal elements in zebrafish, such as the vertebral centra, have also been demonstrated to be mechanically sensitive, and to undergo remodelling in response to load (Fiaz et al 2012 ; Ofer et al 2019 ), which could be regulated by miRs. Finite element models also exist for the zebrafish vertebral column (Newham et al 2019 ; Ofer et al 2019 ).…”
Section: Prospects For Using Zebrafish As a Model For Mechanically Mementioning
confidence: 99%
“…(26) Yet, a recent zebrafish model has proven valuable in the modelling of chd7 dependent CS revealing a reduction in vertebrae mineralization of young larvae. (27) Zebrafish have become increasingly relevant in the study of fundamental bone development and bone related disorders (28)(29)(30) , including scoliosis, osteoporosis, age related osteoarthritis. (31,32) Notably, the spinal structure in zebrafish has been characterized in detail and comprises three major regions: the Weberian apparatus, a specialized structure consisting of the first four vertebrae connecting the auditory system and the swim bladder to amplify sound vibrations, the precaudal vertebrae which are connected to neural arch and spines to form the chest and, the caudal vertebrae of the tail region with neural and hemal arch.…”
Section: Introductionmentioning
confidence: 99%
“…(33) Simplicity of analysis in zebrafish to investigate spinal structures has been used to understand the effects of mechanical loading on bone mineralization. (30,34) Zebrafish have specific advantages in the analysis of skeletal development such as the closely related structure to humans, rapid bone development with first mineralization of vertebrate occurring after only 5 days post fertilization (dpf), as well as ex utero development and transparency of young larvae simplifying the use of in vivo staining and transgenic lines to allow for the analysis of early calcification in zebrafish bony structures. (35)(36)(37)(38) Furthermore, the simplicity of high-throughput drug screening in this teleost model makes the model highly useful for investigating new drug targets and effect on skeletal development.…”
Section: Introductionmentioning
confidence: 99%